Avaliação da remoção de sedimentos pela operação de nivelamento de estradas florestais - Fontana, Carolina Rodrigues; De Paula Lima, Walter; De Barros Ferraz, Silvio Frosini [UNESP] (My University, 2007)
The forest roads construction inevitably causes environmental impacts to adjacent ecosystems and streams. Also the routine activities of roads maintenance may similarly cause environmental impacts of about the same magnitude. The material scraped from the roadway by the motor grader is usually distributed along the roadsides, from where it may easily be washed out toward the streams. Therefore, quantifying the amount of sediments removed during road maintenance activities may provide important information of this stream sedimentation potential. For this purpose, three forest roads were divided in 30 m long segments, marked with leveled stakes. A nylon thread was then stretched across the leveled stakes and the distance from the nylon thread to the road surface was measured before and after the mechanical scraping of the road. The average removal of sediments was of 2,13 cm. Considering the mean density of soil 1,6 g cm -3, the average removal of sediments was of 341 t ha -1 of road. Considering still a 3,9 m wide and 150 m long road as an example, the total amount of removed sediments would be around 19,9 t. Road maintenance, therefore, must be well planned in order to avoid or minimize stream sedimentation.
Evaluation of the amount of sediment removed by the regrading operation in forests roads
Keywords: Forest roads; Maintenance; Removed sediments; Before and after; Mean density; Mechanical scraping; Nylon thread; Road maintenance; Road surfaces; Environmental impact; Polyamides; Rayon; Rivers; Sedimentation; Sedimentology; Roads and streets